2002
DOI: 10.1002/1521-3951(200201)229:2<859::aid-pssb859>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Optical Properties of as-Grown and Proton Irradiated ZnO

Abstract: Conventional photoluminescence spectroscopy (PL) shows several high energy optical transitions within the region 3.072 to 3.4345 eV from as-grown ZnO excited with a 257 nm UV line. Performing inelastic light scattering experiments (ILS), we probed some previously reported modes. Proton implantation caused drastic changes in the excitonic region and generates a broad band centered at about 650 nm (1.9 eV) In addition, we observed from both sides of the ZnO sample implantation-induced high-energy vibrational mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 14 publications
2
8
0
Order By: Relevance
“…Hydrides on the other, nonpolar facets are less stable from DFT calculations, ,, although some calculated geometries found on the (0101̅) facets also explain well the main Zn–H stretching frequency at 1710 cm –1 or the specific Raman feature observed at 1600 cm –1 . This type of hydride on pristine, extended surfaces may be present on ZnO powders where nonpolar facets (101̅0) and (112̅0) are most abundant. , …”
Section: Surface Hydrides On Bulk Oxidesmentioning
confidence: 99%
“…Hydrides on the other, nonpolar facets are less stable from DFT calculations, ,, although some calculated geometries found on the (0101̅) facets also explain well the main Zn–H stretching frequency at 1710 cm –1 or the specific Raman feature observed at 1600 cm –1 . This type of hydride on pristine, extended surfaces may be present on ZnO powders where nonpolar facets (101̅0) and (112̅0) are most abundant. , …”
Section: Surface Hydrides On Bulk Oxidesmentioning
confidence: 99%
“…The wurtzite ZnO with a wide band gap (3.5 eV at very low temperatures and 3.37 eV at the room temperature [1]) is used in blue and ultra-violet (UV) light emitting devices such as diodes and lasers, as well as daylight-blind UV detectors. Due to its large band gap ZnO is suitable for the solar cells and catalysts fabrication.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it finds application in phosphorus, paints, piezoelectric transducers, varistors and transparent conducting films; the later being important for the photovoltaic industry [2]. Optical properties of ZnO have been reported by many authors [1,[3][4][5][6]. Apart from this, lattice dynamics of ZnO has been extensively investigated both experimentally and theoretically ( [7,8] and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…This is the significant difference between our study and previous work regarding the effect of H implantation in ZnO. 6,7 Due to the high implantation energies ranging from 100 keV to 1 MeV in previous studies, the implanted H resided much deeper than the optically active region and showed only the effect of implantation induced damage on the optical properties of ZnO. Half of the hydrogen-implanted samples were annealed in vacuum at 300°C for 15 min.…”
mentioning
confidence: 99%
“…2 a significant decrease in the PL intensity was observed following the He implantation, consistent with previous reports on the highly irradiated ZnO. 6,7 However, the relative intensity of the PL peaks remained unchanged and the peak at 3.364 eV still exhibited the maximum intensity.…”
mentioning
confidence: 99%